Dynamic information acquisition and time-varying uncertainty - Zhifeng Cai (Rutgers University, Department of Economics, 2020)
This paper studies the role of information acquisition in propagating/stabilizing uncertainty shocks in a dynamic financial market. In a static world, uncertainty raises the value of information, which encourages more information acquisition. In a dynamic world, however, uncertainty can depress information acquisi-tion through a dynamic complementarity channel: More uncertainty induces future investors to trade more cautiously. This renders future resale stock price less informative and reduces the value of information today. Due to the dynamic complementarity, transitory uncertainty shocks can have long-lasting impacts. Direct government purchases can stimulate information production, eliminate equilibrium multiplicity, and attenuate the impacts of uncertainty shocks by raising the effective risk-bearing capacity of the informed investors.
Keywords: G12; G14; 330; Information Acquisition; Financial Markets; Dynamic complementarity